MicroRNA-146a promotes IgE class switch in B cells via upregulating 14-3-3σ expression. (December 2017) - Li, Fei; Huang, Yi; Huang, You-Ying; Kuang, Yan-Song; Wei, Yong-Jian; Xiang, Li; Zhang, Xing-Ju; Jia, Zheng-Cai; Jiang, Shan; Li, Jing-Yi; Wan, Ying
Highlights: IgE antibody increases significantly in miR-146a overexpression mice. IgE antibody level is higher in TG B cell cultures than in controls. MiR-146a enhances IgE class switch and secretion in B cells by upregulating 14-3-3σ expression. OVA-specific IgE antibody increase in miR-146a TG mice asthma model. Abstract: B cells play a critical role in immune responses both in physiological and pathological conditions, and microRNAs have been shown to play important roles in regulating B cell proliferation and function. MiR-146a has been shown to modulate T cell immunity, but its function in regulating B cell response remains partially understood. Our previous studies indicated that germinal center (GC) B cells are significantly expanded in miR-146a-overexpressing (TG) mice. In this study, we further characterized the roles of miR-146a in regulating humoral immune responses to specific antigens. We found that the production of IgE antibody were significantly elevated in TG mice, while the antibody affinity maturation of IgM and IgG were similar between TG mice and the normal controls. We further found higher IgE antibody levels in TG B cell culture supernatant than that in normal controls. A global protein expression comparison of B cells from TG mice and the normal controls through TMT proteomic assay showed that 14-3-3σ, a key factor of immunoglobulin class switch DNA recombination (CSR) in B cells, was highly up-regulated in B cells with overexpression of miR-146a, while Smad4, the target of miR-146a, was decreased. Using an asthma model induced by OVA immunization, we further confirmed the increased level of OVA specific IgE antibodies in TG mice. These results demonstrate that miR-146a enhances class switch and secretion of IgE in B cells by upregulating 14-3-3σ expression, and suggest that miR-146a may be a potential target for asthma therapy.